Uncovering MPC Heterogeneity: Insights from US COVID-19 Stimulus Payments - Barnes, Emily (2023)
This paper uncovers heterogeneity in the Marginal Propensity to Consume (MPC) from the three rounds of US COVID-19 stimulus payments. Using a novel clustering method to group households by consumption changes, we estimate the full unconditional MPC distribution via a two-stage least squares approach. This is in contrast to the prevalent practice of linking MPCs solely to observable household attributes. Controls for additional income fluctuations, COVID restrictions, and increased unemployment benefits and child tax credits refine our MPC estimates. Estimated MPCs are smaller than in previous literature, 0.13 to 0.27 for total expenditures with an average MPC of 0.07, indicating limited stimulus payment impact due to heightened uncertainty. MPC heterogeneity persist across expenditure categories, with greater MPCs in durables than nondurables. We identify correlations between the MPC and various observable household characteristics, encompassing income levels, educational attainment, liquid assets, and home ownership status. These insights bear implications for both policy formulation and economic modelling, underlining contextual influences on consumer behaviour and heterogeneity.